Common filaggrin gene mutations and risk of cervical cancer. (February 2015) - Bager, Peter; Wohlfahrt, Jan; Sørensen, Erik; Ullum, Henrik; Høgdall, Claus Kim; Palle, Connie; Husemoen, Lise Lotte Nystrup; Linneberg, Allan; Kjær, Susanne K.; Melbye, Mads; Thyssen, Jacob P.
Abstract: Background. As carriers of filaggrin gene ( FLG ) mutations may have a compromised cervical mucosal barrier against human papillomavirus infection, our primary objective was to study their risk of cervical cancer. Methods. We genotyped 586 cervical cancer patients for the two most common FLG mutations, R501X and 2282del4, using blood from the Copenhagen Hospital Biobank, Denmark. Controls (n = 8050) were genotyped in previous population-based studies. Information on cervical cancer, mortality and emigration were obtained from national registers. Odds ratios (OR) were estimated by logistic regression with adjustment for age at blood sampling, and weighted by the genotype-specific inverse probability of death between diagnosis and sampling. Hazard ratios (HR) were estimated by Cox regression with time since diagnosis as underlying time, and with adjustment for age at diagnosis and stratification by cancer stage. Results. The primary results showed that FLG mutations were not associated with the risk of cervical cancer (6.3% of cases and 7.7% of controls were carriers; OR adjusted 0.81, 95% CI 0.57–1.14; OR adjusted+ weighted 0.96, 95% CI 0.58–1.57). Among cases, FLG mutations increased mortality due to cervical cancer (HR 4.55, 95% CI 1.70–12.2), however, the association was reduced after stratification by cancer stage (HR 2.53, 95% CI 0.84–7.59). Conclusion. Carriage of FLG mutations was not associated with the risk of cervical cancer.